E-Facility For Politeknik Seberang Prai - Nurulaida , Che Mat (UTeM, 2010)
e-facility for Politeknik Seberang Perai is a system that intent to help Politeknik Seberang Perai organization especially Training and Advance Education Unit to give an efficient in providing services to their customers in booking or reservation the facilities that provided. As an overview, this system functioning with the ability to booking online through website. So the customers do not have to go by self to do reservation. The entire customer also can check any update of the facilities from time to time. This system is easier to handle by administrator in order manage all the facilities and information about the facilities. Beside that by using this system, probability to lost any of file is less since they not use paper anymore. All data will be saving in their e-facility database and always can be update if there any reservation comes or something else. The administrator will be receiving all the reservation on time and the customers will get feedback about their reservation also on time in working day. To give the entire customer clear about all the facilities that Politeknik provided, this system also provided a picture and a little bit information about the facilities. This system also give their customers print the report if all the booking process is done. In conclusion this e-facility will help this organization doing their work easier in term to save cost and using more paper like manual system.